Gambaran Kebiasaan Pola Makan pada Ibu Hamil dengan Kekurangan Energi Kronis (KEK) - Hariyani, Salsa Dila Fitria; Hermayanti, Yanti; Yamin, Ahmad; Lukman, Mamat; Solehati, Tetti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the dietary habits of pregnant women with chronic energy deficiency (CHD) at Puskesmas Leles Garut Regency. This research method is descriptive-quantitative by involving 31 pregnant women experiencing first, second, and third trimester SEZ in the age range of 20-35 years at Puskesmas Leles Garut Regency with total sampling. The results showed that 22.6% had bad dietary habits, and 77.4% had good dietary habits. In conclusion, only a small proportion of pregnant women have bad dietary habits because they do not pay attention to the frequency of eating and drinking. Keywords: Chronic Lack Of Energy (CED), Dietary Habits, Pregnant Women